Pengaruh Media Iklan Terhadap Keputusan Membeli Air Minum dalam Kemasan Merk Lam-Lam pada Masyarakat Kota Bima - Nurjoko, Hadi; Putra, Nyoman Nugraha Ardana; Pribadi, Benny Agus (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
The aim of this research is to analyze the influence of online and offline advertising media on decision making to purchase Lam-Lam brand bottled drinking water among the people of Bima City. The research population was all buyers of Lam-Lama mineral drinking water in Bima City, and 53 consumers were used as research samples. The research instrument was a questionnaire using a Likert scale, and the data was analyzed using multiple linear regression analysis techniques. The research results show that the use of online advertising media has a positive and significant influence on the decision of buyers of the Lam-Lam brand of mineral water in Bima City. The use of offline advertising media has a positive and significant effect on the decision of buyers of the Lam-Lam brand of mineral water. The use of online and offline advertising media has a simultaneous and significant influence on the decisions of buyers of Lam-Lam mineral water. The implication of this research is that companies can continuously carry out marketing activities online and offline in a balanced manner so that the product image is increasingly trusted by consumers.